Analysis of Ambulance Ship Design in Karimunjawa Waters reviewed by Stability and Seakeeping - Putra, Gusma Hamdana; Soelistijono, Rachmad Tri; Setyawan, Prasastya Dhohir (Department of Naval Architecture - Diponegoro University, 2024)
The inadequate health facilities in the Karimunjawa Islands region still need attention. In particular, patients who have to be referred to the hospital still have problems in terms of transportation. This research presents the results of simulations of ambulance ship designs adapted to Karimunjawa conditions. A ship with a length of 8 m, width of 2.2 m, height of 1.1 m, and draft height of 0.37 m is analyzed regarding stability and seakeeping referring to IMO HSC Code 2000 Annex 8. Several parameters are determined, such as load, speed, significant wave height, and direction. The results in terms of stability show that loads of 100%, 50%, and 25% are still acceptable. Then, the results from seakeeping show that at a speed of 23 knots and significant wave height, especially in the diagonal wave direction of the ship, it is not acceptable